Offering an American graduate medical HIV course to health care workers in resource-limited settings via the Internet. - Michael H Chung (Public Library of Science (PLoS), 2012)
Background Western accredited medical universities can offer graduate-level academic courses to health care workers (HCWs) in resource-limited settings through the Internet. It is not known whether HCWs are interested in these online courses, whether they can perform as well as matriculated students, or whether such courses are educationally or practically relevant. Methods and findings In 2011, the University of Washington (UW) Schools of Medicine and Nursing offered the graduate course, "Clinical Management of HIV", to HCWs that included a demographic survey, knowledge assessment, and course evaluation. UW faculty delivered HIV clinical topics through ten 2-hour weekly sessions from the perspectives of practicing HIV medicine in developed and developing settings. HCWs viewed lectures through Adobe Acrobat Connect Pro (Adobe Systems, San Jose, CA), and completed online homework on HIV Web Study (http://depts.washington.edu/hivaids/) and online quizzes. HCWs, who met the same passing requirements as UW students by attending 80% lectures, completing ≥90% homework, and achieving a cumulative ≥70% grade on quizzes, were awarded a certificate. 369 HCWs at 33 sites in 21 countries joined the course in 2011, a >15-fold increase since the course was first offered in 2007. The majority of HCWs came from Africa (72%), and most were physicians (41%), nurses (22%), or midlevel practitioners (20%). 298 HCWs (81%) passed all requirements and earned a certificate. In a paired analysis of pre- and post-course HIV knowledge assessments, 56% of HCWs improved their post-course score (p<0.0001) with 27% improving by at least 30%. In the course evaluation, most HCWs rated the course as excellent (53%) or very good (39%). Conclusions This online HIV course demonstrated that opening a Western graduate medical and nursing curriculum to HCWs in resource-limited settings is feasible, popular, and valuable, and may address logistic and economic barriers to the provision of high quality education in these settings.